A Semantics Study of Kidung Yadnya Ceremony in Balinese Hindu Society - Titik Ceriyani Miswaty; Syamsurijjal Syamsurijjal; Muhammad Zaki Pahrul Hadi (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Semantics as the study of meaning,semantics is not only related to the study of meaning but also the relationship between language and culture, one of which is Balinese culture is firmly embedded in Kidung literature. The purpose of this research is that the readers of kidung know the meaning in the lyrics of the kidung Panca Yadnya.By theory Geoffrey Leech in his ‘Semantic- A Study of meaning’(1974) This research focus discusses the analysis of the denotative and connotative meanings contained in the lyrics of Panca Yadnya kidung. a) In the Kidung Panca Yadnya there has 1 positive connotative meaning in the first line of the Kidung Panca Yadnya and 24 denotative meanings.b) In the Rsi Yadnya kidung, there is 1 positive connotative meaning and 26 denotative meanings.c) Kidung Manusa Yadnya has 1 positive connotative and 27 denotative meanings.d) Pitra Yadnya only contains denotative meaning, there are 24 denotative meanings.e) In bhuta yadnya it only contains denotative meaning, there are 10 denotative meanings. This study uses a qualitative descriptive method and this research useful for researchers and future readers, not just reading and singing the kidung Panca Yadnya which has a very close relationship in every Balinese Hindu ceremony.